2015
DOI: 10.1139/cjfas-2014-0225
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bomb-produced14C into fish otoliths. An example of basin-specific rates from the North Pacific Ocean

Abstract: Sagittal otoliths from juvenile Pacific halibut (Hippoglossus stenolepis) of known age were used to create a bombproduced radiocarbon reference chronology for the eastern Bering Sea (EBS) by fitting a coupled-function model to ⌬ 14 C values from each specimen's birth year. The newly created EBS reference chronology was then compared with a reference chronology previously created for Pacific halibut from the Gulf of Alaska (GOA). Adult Pacific halibut age-validation samples from the EBS were also analyzed for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The reduced amplitude of the peak F 14 C within the scale is most likely due to time–averaging of the F 14 C scale signal because of the scale sample size (widths/time) needed for the 14 C measurement. We used a coupled–function model in order to develop a reference curve to use radiocarbon to age lungfish based on fish otolith research [2122, 30]. The model used is shown in Eq 1.…”
Section: Methodsmentioning
confidence: 99%
“…The reduced amplitude of the peak F 14 C within the scale is most likely due to time–averaging of the F 14 C scale signal because of the scale sample size (widths/time) needed for the 14 C measurement. We used a coupled–function model in order to develop a reference curve to use radiocarbon to age lungfish based on fish otolith research [2122, 30]. The model used is shown in Eq 1.…”
Section: Methodsmentioning
confidence: 99%
“…The conflicting results of the ageing methodology validation, depending on the reference chronology used for comparison, highlight the importance of using a reference chronology from the same, or similar, environments with respect to 14 C availability. Cross-basin (Kastelle et al, 2016) and even within-basin (Wischniowski et al, 2015) comparisons have revealed chronologies with distinctly different properties between a validation and a reference data set, demonstrating how misapplication may lead to ageing error. While our study provides a more appropriate bomb radiocarbon reference chronology for use within deeper waters of the SAB, the development of a true region-specific chronology in the SAB consisting of known-age specimens remains necessary to unequivocally distinguish between ageing error and effects of oceanographic processes (Piner & Wischniowski, 2004), and should be a future research goal.…”
Section: Discussionmentioning
confidence: 99%
“…Early on in the history of research utilizing bomb radiocarbon for fish ageing validation, Δ 14 C reference chronologies were limited, but in the past 20 years additional datasets have been developed for multiple regions, so fisheries investigators are no longer extremely limited to a few reference chronologies. The sources of Δ 14 C reference data for ageing validation work are varied, and consist of Δ 14 C measured directly from the atmosphere [ 33 ], from known-age otoliths [ 20 ], from otolith core Δ 14 C with validated ages [ 30 , 34 , 35 ], and from Δ 14 C reported from corals [ 19 , 20 ]. To explain our findings within the context of past research involving the use of temporal Δ 14 C trends and to emphasize the applicability of the north Caribbean reference chronology we established in this study, we identified three main considerations that future ageing validation studies should evaluate to strengthen their findings: 1) evaluation of the applicability of the original goal/objectives and study design of potential Δ 14 C reference studies; 2) evaluation of the applicability of potential Δ 14 C reference data to the region/location where fish samples under evaluation were obtained; and 3) determination of the location of habitat in which the fish species under investigation spends at least the juvenile period that was recorded in the otolith core material extracted for Δ 14 C analysis.…”
Section: Discussionmentioning
confidence: 99%